Participação política das mulheres na Assembleia Legislativa de Rondônia entre 1990 e 1998 - Rodrigues, Érica Andreta (2024)
This dissertation addresses the issue of women's political participation in the Rondônia Legislative Assembly in the 1990 and 1994 elections. Its aims are to understand the relevance of women's political participation in the Rondônia Legislative Assembly in 1990 and 1994; to find out the number of women elected in the above-mentioned elections, the parties they belonged to and the political trajectory of these parliamentarians, identifying their socioeconomic profiles and the agendas they defended during their terms in office; and to investigate the role of the elected women in building a legislative agenda aimed at the people of Rondônia, especially by understanding their involvement in parliamentary committees dealing with issues related to women's rights. The study was carried out in the time frame between 1990 and 1998. This was due to the need to understand the political trajectory faced by the female state deputies elected in Rondônia during this period and their contribution to the population of the region. The search for information on the parliamentarians' activities showed that their projects were aimed at the people of Rondonia in general, especially their municipalities of origin, which were their electoral bases; however, when looking for issues related to the promotion of gender equality and women's rights, no data was found in the annals or in online and printed journals. In conclusion, the history of women's struggle for representation on the political scene in the state of Rondônia has occupied very little space in party politics, as the preponderance of male dominance is visible. The research showed that there are many challenges and achievements in the quest for female representation in the electoral political arena and in decision-making positions in the state of Rondônia. Thus, gender equality was not achieved in electoral politics, especially with regard to the political party structure and leadership positions in the state of Rondônia in the 1990 and 1994 elections.